Effect of Bio-based Adhesive on Tensile Strength and Bending of Balsa Wood Adhesive Joint - Ma'arif, Moch. Syamsul; Putri, Resza Tania; Anam, Khairul (International Journal of Integrated Engineering, 2019)
The aim of this study was to determine the effect of adhesive on tensile strength and bending strength of adhesive joints on balsa wood by varying the type of bio-based adhesive. The use of bio-based adhesive is very potential both as a substitute for synthetic-based adhesive. In this research, adhesive joint was applied using a specimen of balsa wood which was connected with bio-based adhesive which was varied, namely bio-based adhesive from rubber tree sap, sap of jackfruit tree and sap of breadfruit tree. In this study, tensile testing and bending testing were conducted to determine the tensile strength and bending of balsa wood that has been connected using bio-based adhesive variations. The results of the research show that the variation of bio-based adhesive can affect the strength of the structure of balsa wood which is done by adhesive joints because in the variation of bio-based adhesive has different adhesive characteristics so that the binding ability between bio-based adhesive surfaces is different. Fault analysis was carried out after tensile and bending tests to see the effect of bio-based adhesive variations on balsa wood. It is evident that the results of tensile testing on rubber tree sap bio-based adhesive were 28,193 MPa, on jackfruit sap bio-based adhesive was 19,93 MPa and on breadfruit tree bio-based adhesive sap was 15,963 MPa. While the results of bending testing amounted to 23.58 MPa for bio-based adhesive rubber tree sap, on 23.45 MPa for bio-based adhesive sap and breadfruit tree sap at 19.18 MPa.